Effects of erythromycin on pregnancy duration and birth weight in lipopolysaccharide-induced preterm labor in pregnant rats - Celik, H; Ayar, A (Elsevier, 2002)
Objective: The aim of this study was to investigate the effects of erythromycin on pregnancy duration and on live birth weight in lipopolysaccharide (LPS)-induced preterm labor model in rats. Study design: Total of 60 pregnant rats on day 16 of gestation was intraperitoneally injected with 25 mug/kg LPS. Animals were randomly divided into six groups and 20 mg/kg (n = 10), 40 mg/kg (11 = 10), 60 mg/kg (n = 10), 80 mg/kg (n = 10), and 100 mg/ka (n = 10) erythromycin and equal volume of physiological saline (11 = 10) were given intraperitoneally. Injection of LPS-to-vaginal bleeding interval, vaginal bleeding-to-delivery interval, LPS injection-to-delivery interval was monitored and live birth weight of neonates was determined. Statistical analysis was performed using Kruskal-Wallis, Mann-Whitney U-test and Spearman correlation analysis. Results: Intraperitoneal injection of erythromycin to LPS-administered rats caused significant increase in latent period, labor period, total period and live birth weight in a dose dependent manner. Conclusion: These data shows that erythromycin causes prolongation of pregnancy period and increases live birth weight in LPS-induced preterm labor of pregnant rats. (C) 2002 Published by Elsevier Science Ireland Ltd.
Keywords: lipopolysaccharide; preterm labor; erythromycin; birth weight